Astro‐Environmentalism: Towards a Polycentric Governance of Space Debris. Issue 4 (5th June 2021) - Morin, Jean‐Frédéric; Richard, Benjamin
Abstract: The Earth's orbital space is increasingly threatened by debris. It is frequently described as a common‐pool resource vulnerable to a 'tragedy of the commons' scenario. Scholars have suggested ambitious policy proposals to tackle the tragedy of space debris and assure the sustainability of the Earth's orbits. Their proposals can be classified into three categories: hierarchical regulations, economic incentives and property rights. All three categories require some form of central coordination. However, there might be an alternative approach to the problem and other potential solutions. Elinor Ostrom suggested that decentralized, polycentric systems are appropriate for governing common‐pool resources. Anecdotal evidence suggests that a polycentric form of governance can encourage a more sustainable use of the Earth's orbits. Abstract : Anecdotal evidence points to ways in which this polycentric form of governance can encourage a sustainable use of the Earth's orbits. For example, a network of optimal observatories, controlled by universities in Italy, Switzerland and the United States are conducting observation campaigns to monitor space debris.